The Intrusion Detection Solution for Isolated Industrial Control Environments - Liu, I-Hsien; Chen, Nai-Yu; Chou, Pei-Wen; Li, Jung-Shian (Journal of Robotics, Networking and Artificial Life, 2025)
This study explores the implementation of intrusion detection solutions, specifically Snort, in industrial control environments that use network segregation as a security measure. Unlike traditional deployments at gateway ports, our research integrates Snort directly within isolated networks, customized with specific operational technology (OT) rules. The effectiveness of this system was tested using the TWISC@NCKU Critical Infrastructure cybersecurity testbed in Taiwan. This findings indicate that this strategic approach can successfully detect anomalies in network traffic, effectively addressing the common challenge of limited monitoring in segregated network environments.